Analysis on the Influences of Temperature on the Moisture Detection of Transformer Bushings. Issue 1 (June 2020) - Gu, Zhaoliang; Zhu, Wenbing; Zhu, Mengzhao; Xu, Wei; Gao, Zhixin; Yi, Feng
Abstract: Insulation damp is the main cause of transformer bushing failures. Dielectric loss detection, as the most important method to evaluate the insulation state of transformer bushing, has been widely used in the evaluation of transformer bushing dampness. But its accuracy of detection will be affected by temperature and other environmental factors. The real capacitor transformer bushings have been taken as the research object to simulate the real situations of transformer bushing dampness in this paper. The relationship between Dielectric loss values and temperature of transformer bushings with different moisture concentrations have been obtained. And the influences of temperature on the moisture detection of transformer bushings are also studied. These results can provide reference for the accurate dielectric loss detection of transformer bushings and the diagnosis of dampness degree.